2016
DOI: 10.1080/00380768.2016.1244652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of groundwater level fluctuation on soil respiration rate of tropical peatland in Central Kalimantan, Indonesia

Abstract: Soil respiration (SR) rate was measured at the burned land (BL), the cropland (CL), the forest land (FL) and the grassland (GL) of a tropical peatland in Central Kalimantan, Indonesia from 2002 to 2011 for the purpose of analysis with a relation to the drying and rewetting. The SR rate was fitted with groundwater level (GWL) to the equation of log(SR) = α-β × GWL using hierarchical Bayesian analysis where α and β were regression coefficients classified by GWL changing directions (drying, rewetting and fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 68 publications
9
35
2
1
Order By: Relevance
“…Higher soil temperatures have been reported to enhance SR in tropical peatland (e.g., Melling et al, 2005;Ali et al, 2006;Ishikura et al, 2017); however, our results showed only a weak positive correlation between PD and soil temperature (p < 0.05) at DB, which lacked a canopy. Moreover, our results suggest that PD could predominantly be explained by variation in GWL.…”
Section: Factors Affecting Oxidative Peat Decompositioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Higher soil temperatures have been reported to enhance SR in tropical peatland (e.g., Melling et al, 2005;Ali et al, 2006;Ishikura et al, 2017); however, our results showed only a weak positive correlation between PD and soil temperature (p < 0.05) at DB, which lacked a canopy. Moreover, our results suggest that PD could predominantly be explained by variation in GWL.…”
Section: Factors Affecting Oxidative Peat Decompositioncontrasting
confidence: 91%
“…3a and b). A large CO2 efflux in November 2014 at DF was removed from the correlation analysis, because rewetting can temporarily enhance decomposition or respiration during a dry period (as detailed in Ishikura et al, 2017). At DB, PD peaked at the beginning of the dry period and decreased with decreasing GWL until GWL reached a depth of -1.4 m. By contrast, PD increased with decreasing GWL in the wet season, when there was a relatively high GWL (Fig.…”
Section: Relationship Of Pd With Gwl and Prediction Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Draining the excess of water to provide aerobic layer can lower the groundwater table and increase air and soil temperature. The tendency of higher soil temperature at deeper groundwater level was reported by Ishikura et al (2017) and Wakhid et al (2018). As a result, microbial activities in peat decomposition process increase and release a significant amount of carbon to the atmosphere.…”
Section: Discussionsupporting
confidence: 55%
“…Due to the limitations of field studies, the controlling factors of soil CO 2 efflux are not well understood at the process level. For example, it was reported that no significant relationship exists between R S and groundwater level (GWL) (Jauhiainen et al, 2008), probably due to the disconnection of capillary force under dry conditions, resulting in soil moisture in the topsoil becoming decoupled from the GWL (Ishikura et al, 2017). Soil moisture in the topsoil can be a better predictor than GWL for soil CO 2 efflux (Melling et al, 2005(Melling et al, , 2013a, because soil moisture is affected more by capillary rise than GWL when a peat soil is compacted (Price, 1997;Michel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%